We will discuss here about the expansion of (a ± b)\(^{3}\).
(a + b)\(^{3}\) = (a + b) ∙ (a + b)\(^{2}\)
= (a + b)(a\(^{2}\) + 2ab + b\(^{2}\))
= a(a\(^{2}\) + 2ab + b\(^{2}\)) + b(a\(^{2}\) + 2ab + b\(^{2}\))
= a\(^{3}\) + 2a\(^{2}\)b + ab\(^{2}\) + ba\(^{2}\) + 2ab\(^{2}\) + b\(^{3}\)
= a\(^{3}\) + 3a\(^{2}\)b + 3ab\(^{2}\) + b\(^{3}\).
(a - b)\(^{3}\) = (a - b) ∙ (a - b)\(^{2}\)
= (a - b)(a\(^{2}\) - 2ab + b\(^{2}\))
= a(a\(^{2}\) - 2ab + b\(^{2}\)) - b(a\(^{2}\) - 2ab + b\(^{2}\))
= a\(^{3}\) - 2a\(^{2}\)b + ab\(^{2}\) - ba\(^{2}\) + 2ab\(^{2}\) - b\(^{3}\)
= a\(^{3}\) - 3a\(^{2}\)b + 3ab\(^{2}\) - b\(^{3}\).
Corollaries:
(a + b)\(^{3}\) = a\(^{3}\) + 3ab(a + b) + b\(^{3}\) = a\(^{3}\) + b\(^{3}\) + 3ab(a + b)
(a - b)\(^{3}\) = a\(^{3}\) – 3ab(a - b) - b\(^{3}\) = a\(^{3}\) - b\(^{3}\) - 3ab(a - b)
(a + b)\(^{3}\) – (a\(^{3}\) + b\(^{3}\)) = 3ab(a + b)
(a - b)\(^{3}\) – (a\(^{3}\) - b\(^{3}\)) = 3ab(a - b)
a\(^{3}\) + b\(^{3}\) = (a + b)\(^{3}\) - 3ab(a + b)
a\(^{3}\) - b\(^{3}\) = (a - b)\(^{3}\) + 3ab(a - b)
From Expansion of (a ± b)\(^{3}\) to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
Jan 17, 25 12:34 PM
Jan 17, 25 01:46 AM
Jan 17, 25 01:17 AM
Jan 17, 25 12:01 AM
Jan 15, 25 01:54 PM
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.